A AND (B OR C) AND (NOT B)

asked by guest
on Mar 24, 2025 at 11:16 pm



MathBot Answer:

Logic Expression
Symbol: A(BC)¬BA \wedge \left(B \vee C\right) \wedge \neg B
Text: A and (B or C) and not BA \text{ and } \left(B \text{ or } C\right) \text{ and } \text{not } B


Classification contingency


Truth Table

Legend

AABBCCBCB \vee C¬B\neg BA(BC)¬BA \wedge \left(B \vee C\right) \wedge \neg B
111100
110100
101111
100010
011100
010100
001110
000010
T/F

SimplificationA(BC)¬BAC¬BRedundancy Law (2)\begin{gathered} A \wedge \left(B \vee C\right) \wedge \neg B & \equiv & A \wedge C \wedge \neg B & \text{Redundancy Law (2)} \end{gathered} Note: Solution may not be as simplified as possible.


Conjunctive Normal FormAC¬BA \wedge C \wedge \neg B


Note 1: These equivalences and tautologies are used to generate the above steps.
Note 2: Two logical statements are logically equivalent if they always produce the same truth value. Consequently, p ≡ q is same as saying p ↔ q is a tautology. EquivalenceAbsorption Lawp(pq)pp(pq)pBiconditional Equivalencepq(p¬q)(¬pq)pq(pq)(¬p¬q)Biconditional SimplificationppTruepTruepp¬pFalsepFalse¬pComplement Lawp¬pFalsep¬pTrueConditional Equivalencepq¬pqConditional SimplificationppTruepTrueTruepFalse¬pp¬p¬pTrueppFalsepTrue¬pppConsensus Law(pq)(¬pr)(qr)(pq)(¬pr)(pq)(¬pr)(qr)(pq)(¬pr)De Morgan’s Law¬(pq)¬p¬q¬(pq)¬p¬qDistributive Lawp(qr)(pq)(pr)p(qr)(pq)(pr)(pq)(rs)(pr)(ps)(qr)(qs)(pq)(rs)(pr)(ps)(qr)(qs)Domination LawpTrueTruepFalseFalseDouble Negation Law¬(¬p)pIdempotent LawppppppIdentity LawpTrueppFalsepNANDpq¬(pq)Negation Law¬TrueFalse¬FalseTrueNORpq¬(pq)Negation of Biconditional Equivalence¬(pq)(pq)(¬p¬q)¬(pq)(p¬q)(¬pq)Negation of Conditional Equivalence¬(pq)p¬qRedundancy Law (1)(pq)(p¬q)p(pq)(p¬q)pRedundancy Law (2)p(¬pq)pqp(¬pq)pqXORpq(pq)(¬p¬q)pq(p¬q)(¬pq)XOR SimplificationppFalsepTrue¬pp¬pTruepFalsepXNORpq¬(pq)\begin{array}{c|c}\textbf{Equivalence} \\ \hline \text{Absorption Law} & \begin{gathered} p \wedge \left(p \vee q\right) \equiv p \\ p \vee \left(p \wedge q\right) \equiv p \end{gathered} \\ \hline \text{Biconditional Equivalence} & \begin{gathered} p \leftrightarrow q \equiv \left(p \vee \neg q\right) \wedge \left(\neg p \vee q\right) \\ p \leftrightarrow q \equiv \left(p \wedge q\right) \vee \left(\neg p \wedge \neg q\right) \end{gathered} \\ \hline \text{Biconditional Simplification} & \begin{gathered} p \leftrightarrow p \equiv \text{True} & p \leftrightarrow \text{True} \equiv p \\ p \leftrightarrow \neg p \equiv \text{False} & p \leftrightarrow \text{False} \equiv \neg p \end{gathered} \\ \hline \text{Complement Law} & \begin{gathered} p \wedge \neg p \equiv \text{False} \\ p \vee \neg p \equiv \text{True} \end{gathered} \\ \hline \text{Conditional Equivalence} & p \rightarrow q \equiv \neg p \vee q \\ \hline \text{Conditional Simplification} & \begin{gathered} p \rightarrow p \equiv \text{True} & p \rightarrow \text{True} \equiv \text{True} & p \rightarrow \text{False} \equiv \neg p \\ p \rightarrow \neg p \equiv \neg p & \text{True} \rightarrow p \equiv p & \text{False} \rightarrow p \equiv \text{True} \\ \neg p \rightarrow p \equiv p\end{gathered} \\ \hline \text{Consensus Law} & \begin{gathered} \left(p \vee q\right) \wedge \left(\neg p \vee r\right) \wedge \left(q \vee r\right) \equiv \left(p \vee q\right) \wedge \left(\neg p \vee r\right) \\ \left(p \wedge q\right) \vee \left(\neg p \wedge r\right) \vee \left(q \wedge r\right) \equiv \left(p \wedge q\right) \vee \left(\neg p \wedge r\right) \end{gathered} \\ \hline \text{De Morgan's Law} & \begin{gathered} \neg \left(p \wedge q\right) \equiv \neg p \vee \neg q \\ \neg \left(p \vee q\right) \equiv \neg p \wedge \neg q \end{gathered} \\ \hline \text{Distributive Law} & \begin{gathered} p \wedge \left(q \vee r\right) \equiv \left(p \wedge q\right) \vee \left(p \wedge r\right) \\ p \vee \left(q \wedge r\right) \equiv \left(p \vee q\right) \wedge \left(p \vee r\right) \\ \left(p \vee q\right) \wedge \left(r \vee s\right) \equiv \left(p \wedge r\right) \vee \left(p \wedge s\right) \vee \left(q \wedge r\right) \vee \left(q \wedge s\right) \\ \left(p \wedge q\right) \vee \left(r \wedge s\right) \equiv \left(p \vee r\right) \wedge \left(p \vee s\right) \wedge \left(q \vee r\right) \wedge \left(q \vee s\right) \end{gathered} \\ \hline \text{Domination Law} & \begin{gathered} p \vee \text{True} \equiv \text{True} \\ p \wedge \text{False} \equiv \text{False} \end{gathered} \\ \hline \text{Double Negation Law} & \neg \left(\neg p\right) \equiv p \\ \hline \text{Idempotent Law} & \begin{gathered} p \wedge p \equiv p \\ p \vee p \equiv p \end{gathered} \\ \hline \text{Identity Law} & \begin{gathered} p \wedge \text{True} \equiv p \\ p \vee \text{False} \equiv p \end{gathered} \\ \hline \text{NAND} & p \uparrow q \equiv \neg \left(p \wedge q\right) \\ \hline \text{Negation Law} & \begin{gathered} \neg \text{True} \equiv \text{False} \\ \neg \text{False} \equiv \text{True} \end{gathered} \\ \hline \text{NOR} & p \downarrow q \equiv \neg \left(p \vee q\right) \\ \hline \text{Negation of Biconditional Equivalence} & \begin{gathered} \neg \left(p \leftrightarrow q\right) \equiv \left(p \vee q\right) \wedge \left(\neg p \vee \neg q\right) \\ \neg \left(p \leftrightarrow q\right) \equiv \left(p \wedge \neg q\right) \vee \left(\neg p \wedge q\right) \end{gathered} \\ \hline \text{Negation of Conditional Equivalence} & \neg \left(p \rightarrow q\right) \equiv p \wedge \neg q \\ \hline \text{Redundancy Law (1)} & \begin{gathered} \left(p \vee q\right) \wedge \left(p \vee \neg q\right) \equiv p \\ \left(p \wedge q\right) \vee \left(p \wedge \neg q\right) \equiv p \end{gathered} \\ \hline \text{Redundancy Law (2)} & \begin{gathered} p \wedge \left(\neg p \vee q\right) \equiv p \wedge q \\ p \vee \left(\neg p \wedge q\right) \equiv p \vee q \end{gathered} \\ \hline \text{XOR} & \begin{gathered} p \oplus q \equiv \left(p \vee q\right) \wedge \left(\neg p \vee \neg q\right) \\ p \oplus q \equiv \left(p \wedge \neg q\right) \vee \left(\neg p \wedge q\right) \end{gathered} \\ \hline \text{XOR Simplification} & \begin{gathered} p \oplus p \equiv \text{False} & p \oplus \text{True} \equiv \neg p \\ p \oplus \neg p \equiv \text{True} & p \oplus \text{False} \equiv p \end{gathered} \\ \hline \text{XNOR} & p \odot q \equiv \neg \left(p \oplus q\right) \end{array} TautologyConjunctive Simplification(pq)p(pq)qContradiction¬(p¬p)Contrapositive(pq)(¬q¬p)Disjunctive Additionp(pq)q(pq)Disjunctive Syllogism((pq)¬q)p((pq)¬p)qHypothetical Syllogism((pq)(qr))(pr)Modus Ponens(p(pq))qModus Tollens(¬q(pq))¬p\begin{array}{c|c}\textbf{Tautology} \\ \hline \text{Conjunctive Simplification} & \begin{gathered} \left(p \wedge q\right) \rightarrow p \\ \left(p \wedge q\right) \rightarrow q \end{gathered} \\ \hline \text{Contradiction} & \neg \left(p \wedge \neg p\right) \\ \hline \text{Contrapositive} & \left(p \rightarrow q\right) \leftrightarrow \left(\neg q \rightarrow \neg p\right) \\ \hline \text{Disjunctive Addition} & \begin{gathered} p \rightarrow \left(p \vee q\right) \\ q \rightarrow \left(p \vee q\right) \end{gathered} \\ \hline \text{Disjunctive Syllogism} & \begin{gathered} \left(\left(p \vee q\right) \wedge \neg q\right) \rightarrow p \\ \left(\left(p \vee q\right) \wedge \neg p\right) \rightarrow q \end{gathered} \\ \hline \text{Hypothetical Syllogism} & \left(\left(p \rightarrow q\right) \wedge \left(q \rightarrow r\right)\right) \rightarrow \left(p \rightarrow r\right) \\ \hline \text{Modus Ponens} & \left(p \wedge \left(p \rightarrow q\right)\right) \rightarrow q \\ \hline \text{Modus Tollens} & \left(\neg q \wedge \left(p \rightarrow q\right)\right) \rightarrow \neg p \end{array}